The pace and shape of senescence in angiosperms. (24th April 2013) - Baudisch, Annette; Salguero‐Gómez, Roberto; Jones, Owen R.; Wrycza, Tomasz; Mbeau‐Ache, Cyril; Franco, Miguel; Colchero, Fernando; Hutchings, Michael
Summary Demographic senescence, the decay in fertility and increase in the risk of mortality with age, is one of the most striking phenomena in ecology and evolution. Comparative studies of senescence patterns of plants are scarce, and consequently, little is known about senescence and its determinants in the plant kingdom. Senescence patterns of mortality can be classified by distinguishing between two metrics: pace and shape. The pace of mortality captures the speed at which life proceeds and can be measured by life expectancy, while the shape of mortality captures whether mortality increases ('senescence'), decreases ('negative senescence') or remains constant over age ('negligible senescence'). We extract mortality trajectories from ComPADRe III, a data base that contains demographic information for several hundred plant species. We apply age‐from‐stage matrix decomposition methods to obtain age‐specific trajectories from 290 angiosperm species of various growth forms distributed globally. From these trajectories, we survey pace and shape values and investigate how growth form and ecoregion influence these two aspects of mortality using a Bayesian regression analysis that accounts for phylogenetic relationships using a resolved supertree. In contrast to the animal kingdom, most angiosperms (93%) show no senescence. Senescence is observed among phanerophytes (i.e. trees), but not among any other growth form (e.g. epiphytes, chamaephytes or cryptopyhtes). Yet, most phanerophytes (81%) do not senesce. We find that growth form relates to differences in pace, that is, life span, as woody plants are typically longer lived than nonwoody plants, while differences in shape, that is, whether or not angiosperms senesce, are related to ancestral history. Synthesis: The age trajectory of mortality captures a fundamental life‐history pattern for a species that is crucial to ecological understanding. We contribute to ecological knowledge by surveying these patterns across angiosperms. The novelty and strength of our study lies in the comprehensiveness of the data set, the use of a novel Bayesian analysis that accounts for phylogenetic history and in the distinction between metrics of pace and shape as two separate aspects of mortality. We believe that our approach could prove useful in future comparative studies of mortality patterns.